Open Educational Resources (OER) for School Education - Pitroda, Sameena (JOURNAL OF INDIAN EDUCATION, 2011)
Open Educational Resources (OER) are transforming the landscape of school education by providing free and adaptable learning materials. This initiative promotes inclusivity, accessibility, and equity in education, enhancing the quality of learning for all students. OER for school education encompasses a wide range of resources, including textbooks, lesson plans, multimedia content, and interactive modules. This paper explores the benefits, challenges, and initiatives related to OER in school education, highlighting the potential for OER to revolutionize the way we teach and learn.